2018
DOI: 10.1037/adb0000373
|View full text |Cite
|
Sign up to set email alerts
|

Triple trajectories of alcohol use, tobacco use, and depressive symptoms as predictors of cannabis use disorders among urban adults.

Abstract: Heavy cannabis use is associated with a wide array of physical, mental, and functional problems. Therefore, cannabis use disorders (CUDs) may be a major public health concern. Given the adverse health consequences of CUDs, the present study seeks to find possible precursors of CUDs. The current study consisted of 5 waves of data collection from the Harlem Longitudinal Development Study. Among 816 participants, about half are African Americans (52%), and the other half are Puerto Ricans (48%). We used Mplus to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…Strong associations exist between depression and anxiety and previous studies have suggested that more than 50% of patients with an anxiety disorder had depression 32 . An association between tobacco use and depression has also been shown by multiple previous studies 33‐35 and cigarette use was positively associated with depressive symptoms among young people such as college students 36 . Phenotype_B (n = 4687; 52.65%) included most patients (mean (SD) age, 68.44 (19.09) years) in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Strong associations exist between depression and anxiety and previous studies have suggested that more than 50% of patients with an anxiety disorder had depression 32 . An association between tobacco use and depression has also been shown by multiple previous studies 33‐35 and cigarette use was positively associated with depressive symptoms among young people such as college students 36 . Phenotype_B (n = 4687; 52.65%) included most patients (mean (SD) age, 68.44 (19.09) years) in our study.…”
Section: Discussionsupporting
confidence: 81%
“…In general, the differences have been observed in previous studies (e.g., association of smoking with sex 10,11,14 , low education 14,27 , unemployment 27 , low socioeconomic status 23 , and alcohol or substance use 9,28 ), though mostly among adolescents, young adults, or non-general population samples. Moreover, most previous studies have only been able to assess a limited number of background variables, without a longitudinal multivariable approach concerning both smoking behaviour and background variables.…”
Section: Discussionmentioning
confidence: 70%
“…Due to these findings, further examination of decision-making strategies of cannabis users during the EEfRT via computational modeling is warranted. Similar to Lawn et al, (2016), we did not exclude tobacco or alcohol users from our sample, and, thus, our findings are generalizable to the general population of cannabis users who are likely to have comorbid alcohol and tobacco use (odds ratios range from 1.6 to 3.0; Hammond, Chaney, Hendrickson, & Sharma, 2020;Hayley, Stough, & Downey, 2017;Lee, Brook, & Kim, 2018). While Lawn et al (2016) attributed the absence of group differences to the likelihood that they did not control for other substance use in their control group, the difference between groups in the current study on overall % hard trials remained even when controlling for tobacco and alcohol use.…”
Section: Discussionmentioning
confidence: 99%